Thankot Active Fault in the Kathmandu Valley, Nepal Himalaya - Asahi, Katsuhiko (Journal of Nepal Geological Society, 2003)
A WNW-ESE trending active fault (ca. 6 km long) named as Thankot Active Fault (TAF) has been recognized in the south western part of the Kathmandu Valley. The fault with low scarps, flexure, fault trench, minor graben, and sag pond cuts through the terraces and alluvial fans along the foot of the northern flank of the Chandragiri Range. Based on the morphotectonic features and configuration along the fault, the fault has been identified as a reverse fault on the southwestern area but shows normal faulting on the northeast. The vertical rate of displacement along the fault is less than 1 mm a-1. The Thankot Active Fault runs counter to the Chitlang Fault another active fault just outside Kathmandu Valley. The sense of these two faults may imply a conjugate system putting the Chandragiri Range between a pair of active faults.